Expanding our Understanding of Atypical Antipsychotics: Acute Urinary Retention Secondary to Olanzapine - Hannah Mirzakhani; Mariam Rahim; Jacob Mathew (Case Reports in Psychiatry)
Antipsychotics are considered the most efficacious drugs in the treatment of schizophrenia and other psychotic disorders. While clinicians monitor for the onset of extrapyramidal symptoms (EPSs), many do not consider the antimuscarinic and histaminergic side effects that can occur with second generation antipsychotics. We present the case of a 62-year-old male who presented with acute urinary retention that was found to be due to the recent initiation of olanzapine. Gradual cessation of the medication and follow-up with urology revealed resolution of his symptoms. With the increasing demand for psychiatric care but limited psychiatric resources, more and more primary care physicians find themselves dealing with the complex challenges of mental illness and managing antipsychotic medications. As a result, coordinating care among multiple specialties and understanding the full profile of side effects that are associated with psychiatric medications can yield quicker diagnoses and improve patient care.